Antecedents of intention to stay with the mediating effects of work-family factors among single mothers - Noraani Mustapha; Aminah Ahmad; Jegak Uli; Khairuddin Idris (2011)
Employee loyalty has long been an issue in the field of human resource since it is related to behaviors such as attendance, turnover, organizational citizenship, lost of organizational memory and effectiveness. This study was conducted to test the mediating effects of workfamily facilitation and family satisfaction on the relationship between family-friendly work environment as the independent variable and intention to stay as the dependent variable. By using self-administered research questionnaire, data was collected from 240 mid-age single mother employees in Klang Valley, Malaysia. Samples were selected through simple random sampling method whereby six out of 24 single mother associations were selected to obtain research samples. Descriptive statistical analysis was conducted to describe the respondents. Pearson Product Moment Correlation was used to determine the relationships among variables and Structural Equation Modeling using AMOS version 16.0 was utilized to verify the presence of mediation effects. Then the Soble’s z-test was used to test whether the mediators carry the effect of the independent variable on the dependent variable. The findings indicated that there were positive significant relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize family-friendly work factors along with work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees.